1995
DOI: 10.1128/jvi.69.1.198-205.1995
|View full text |Cite
|
Sign up to set email alerts
|

Substrate determinants for cleavage in cis and in trans by the hepatitis C virus NS3 proteinase

Abstract: Processing of the hepatitis C virus polyprotein is accomplished by a series of cotranslational and posttranslational cleavages mediated by host cell signalases and two virally encoded proteinases. Of these the NS3 proteinase is essential for processing at the NS3/4A, NS4A/4B, NS4B/5A, and NS5A/5B junctions. Processing between NS3 and NS4A occurs in cis, implying an intramolecular reaction mechanism, whereas cleavage at the other sites can also be mediated in trans. Sequence analysis of the amino termini of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…These critical cleavage events in theory could occur through intraor intermolecular (i.e., cis or trans) mechanisms. Biochemical evidence of cis-cleavages at the hepaci-and pestivirus NS3-NS4A and flavivirus NS2B-NS3 has been reported for various virus systems (10,15,47,59). The capture of the post-cis-cleavage state in HCV (29) and in CSFV (this study) has provided valid evidence to further support the existence of cis-cleavage at the NS3-NS4A junction for the Hepacivirus and Pestivirus genera.…”
Section: Discussionsupporting
confidence: 73%
“…These critical cleavage events in theory could occur through intraor intermolecular (i.e., cis or trans) mechanisms. Biochemical evidence of cis-cleavages at the hepaci-and pestivirus NS3-NS4A and flavivirus NS2B-NS3 has been reported for various virus systems (10,15,47,59). The capture of the post-cis-cleavage state in HCV (29) and in CSFV (this study) has provided valid evidence to further support the existence of cis-cleavage at the NS3-NS4A junction for the Hepacivirus and Pestivirus genera.…”
Section: Discussionsupporting
confidence: 73%
“…During infection and also during the experimental setup of in vitro translation, the increase in local concentration of the substrate that the cis cleavage provides may make it the predominant pathway. This situation is different from the cleavage of the hepatitis C virus (HCV) polyprotein site NS3/ 4A, which is obligatorily cleaved in cis (4,21). The sequence of the NS3/4A site is distinct from those of the other HCV cleavage sites and more tolerant for substitutions, due to additional interactions involved in recognition of the site and due to protein folding (47).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, a consensus sequence would read D/E-X-X-X-X-C/T↓S/A-X-X-X (where 'X' is variable). Mutagenesis studies of the serine proteinase-dependent sites have revealed that: first, the acidic P6 residue is dispensable; second, except for the structure-disturbing Pro, the P1' position is tolerant towards substitutions; and third, the P1-Cys is the dominant determinant for cleavage efficiency [84,92,113,117,118]. Alteration of its sulphydryl function and/or bulkiness or chirality resulted in a 20-to 12 500-fold loss of cleavage efficiency [105,115,116].…”
Section: Substrate Specificity Of the Ns3/4a Proteinasementioning
confidence: 99%
“…Alteration of its sulphydryl function and/or bulkiness or chirality resulted in a 20-to 12 500-fold loss of cleavage efficiency [105,115,116]. Interestingly, the severity of substitutions on processing increased with the distance from the proteinase, with the NS3/4A site being much more tolerant than the NS4A/B, NS4B/5A and NS5A/B sites [92,117]. This result probably reflects the different mechanisms operating at the various sites.…”
Section: Substrate Specificity Of the Ns3/4a Proteinasementioning
confidence: 99%